Lost-wax or laser sintering? Findings on marginal and internal adaptation of metallic copings (Research, Society and Development, 2021)
Marginal and internal adaptation are parameters of crucial importance to the success of prosthetic crowns. Automatized process creates an expectative of superior or equivalent results compared to restorations manufactured ​​by conventional lost-wax technique. The purpose of this study was to evaluate the marginal adaptation and internal adaptation (cement space) of metal-ceramic crown copings produced by lost-wax (LW) and direct metal laser sintering (DMLS) techniques. An artificial lower first molar was prepared for a full crown, duplicated in plaster and scanned. Twenty metal-ceramic crown copings were fabricated in cobalt-chromium by the two techniques (n=10). The copings were filled with low viscosity silicone and seated on the prepared tooth, resulting in a replica of the internal space. The pellicle formed was embedded in heavy body silicone, sectioned and captured by means of a stereomicroscope at 50x magnification, according to replica technique (RT). Shapiro-Wilk test followed by Holm-Sidak test were used for statistical analysis (α=.05). Marginal adaptation presented no difference between LW (101.5 ± 41.6) and DMLS (86.3 ± 39.9) groups (p=0.24). Conventional LW technique showed significantly lower occlusal (p